Use of Fatty Acids From Aquatic Prey Varies With Foraging Strategy - Twining, Cornelia W.; Parmar, Tarn Preet; Mathieu-Resuge, Margaux; Kainz, Martin J.; Shipley, Jeremy Ryan; Martin-Creuzburg, Dominik (Frontiers in Ecology and Evolution, 2021)
1. Across ecosystems, resources vary in their nutritional composition and thus their dietary value to consumers. Animals can either access organic compounds, such as fatty acids, directly from diet or through internal biosynthesis, and the extent to which they use these two alternatives likely varies based on the availability of such compounds across the nutritional landscape. Cross-ecosystem subsidies of important dietary nutrients, like omega-3 long-chain polyunsaturated fatty acids (n-3 LC-PUFA), may provide consumers with the opportunity to relax the demands of synthesis and rely upon dietary flexibility rather than internal metabolic processes. 2. Here, we examined how dietary flexibility and distance from a lake influenced the degree to which generalist insectivores relied upon dietary n-3 LC-PUFA from emergent aquatic insects versus n-3 LC-PUFA synthesized from precursor compounds found in terrestrial insects. 3. We used bulk and compound-specific stable isotope analyses to understand spider and insectivorous bird (Blue Tit; Cyanistes caeruleus) reliance on aquatic and terrestrial resources, including dietary PUFA sources, along a riparian to upland gradient from a lake. We simultaneously investigated n-3 LC-PUFA synthesis ability in nestlings using 13C fatty acid labelling. 4. We found that riparian spiders took advantage of emergent aquatic insect subsidies, deriving their overall diet and their n-3 PUFA from aquatic resources whereas nestling birds at all distances and upland spiders relied upon terrestrial resources, including PUFA. Our 13C labelling experiment demonstrated that nestling birds were able to synthesize the n-3 LC-PUFA docosahexaenoic acid from the dietary precursor α-linolenic acid, suggesting that they are not limited by aquatic resources to satisfy their LC-PUFA requirements. 5. Overall, this study suggests that habitat generalist insectivores vary in the degree to which they can shift diet to take advantage of high-quality aquatic resources depending upon both their foraging flexibility and internal synthesis capacity.